Curating creative Communities of Practice: The role of ambiguity - Michael Kaethler (Journal of Organization Design, 2019)
Communities of Practice (CoPs), it is argued, are loci for creativity, innovation and problem-solving. Instigating a CoP and harnessing this creative energy from an external position (be it institutional or individual) is, however, problematic. Literature surrounding CoPs emphasises the delicate manner in which they are formed and sustained. Those instigating these communities from an external position, such as curators, managers, or educators, do so at the risk of undermining some of CoPs' fundamental qualities. Namely: the fluid social relations, the level of informality and the processes of self-selection and moderation that characterise CoPs. Asking the question 'how, if possible, can one instigate creatively-oriented CoPs?'-in particular those composed of experts working within limited timeframes-this paper analyses eleven newly formed groups partaking in an experimental design biennial (BIO50) organised to foster collaborative learning and practice. The study focuses on the relationship between a curatorial structure with high degrees of ambiguity and participant collaboration. The paper provides practical implications and theoretical elaborations for those seeking to organise creative collaborations.
Keywords: 650; Curating; Ambiguity; Creativity; Collaboration; Community of Practice